EPIDEMIOLOGY UPDATE OF HELMINTHIASIS IN INDONESIA - Reqgi First Trasia (Insights in Public Health Journal, 2021)
Helminthiasis are still a health problem in Indonesia. Although not deadly, helminth infections will slowly affect children's health and productivity through a decrease in nutritional status. The chronic clinical course and tend to be asymptomatic causes helminthiasis to be classified as a neglected tropical disease. Research on the epidemiology of helminthiasis has been carried out in several regions in Indonesia. However, there has not been a comprehensive review to see the epidemiology aspects of helminthiasis. This article will discuss in detail how helminth infections influence the host to increase the incidence of malnutrition and its impact on children's health. Although this is not an emergency and a condition, the risk factors will lead the child to a state of chronic helminthiasis and transmission to other children which will have a negative impact on public health.